The exclusivity of inclusion: global construction of vulnerable and apolitical victimhood in peace agreements - Jamar, Astrid (International journal of transitional justice, 2021)
This article examines the articulation of commitments towards inclusion and victimhood agreed upon within peace processes. It builds on original and comprehensive empirical material to scrutinize provisions for victims’ inclusion in all peace agreements signed from 1990 to 2016. In addition to methodological innovations, this approach offers a global picture and theoretical insights from intersectional, feminist and decolonial perspectives. The article finds that the conceptualizations of ‘victimhood’ and ‘inclusion’ are mostly gender and politically blind; inclusion efforts are often pursued without consideration for political and socio-cultural issues. Still within such conceptual ambiguity, qualifiers and types of efforts provided for inclusion produce the global construction of victimhood as vulnerable, innocent and apolitical. Such conceptual construction negates the complex and fluid political identity of victims; and reproduces sexist, heteronormative and subordinating binaries. The adopted language magnifies vulnerabilities within peace agreements, and provides for actions that do not create space for active participation within these institutional settings. This article contributes to the growing theoretical and policy discussions about inclusion by exposing the ‘inclusion conundrum,’ i.e., inevitable exclusivity - shaped by different forms of sexism, classism and racism - entailed in practices that inquire and decide which victims should be included. Building on these observations, I call for an ontological re-articulation of inclusion by reshaping transitional institutional responses that embrace fluidity rather than reproduce oppression exacerbated by violent conflicts.